Erosion susceptibility model applied to the management of railways. Case study: Tietê - Sorocaba hydrographic basin train network - Souza, Natália Costa; Lollo, José Augusto [UNESP]; Almeida Filho, Gerson Salviano (My University, 2020)
The occurrence of accelerated erosive events associated to the implantation of transport systems is one of the main socioenvironmental problems encountered by brazilian concessionaires. Studies related to the analyzes of development dynamics of erosive processes are inserted in theoretical and methodological consecrated environmental approaches in the areas of Geosciences. In several areas of knowledge and in the most varied approaches able of supporting processes of analysis, monitoring and control of environmental risks, statistical techniques of multivariate data analysis associated with the use of geographic information systems have been widely used tools. This research proposes the combination of the use of geotechnologies and Multivariate Data Analysis to analyze the levels of susceptibility to erosion in the terrain corresponding to the surroundings of the Malha Paulista railway. The results provided the reading of the selected soil environmental characteristics for the composition of the indicator and the analysis of the quantification of the areas classified into levels of susceptibility. Obtaining information that validated the final result of the indicator was a differential of the research. Based on the total erosive processes analyzed and on the defined susceptibility classes, it is possible to state that the final mapping presented a precision of 91.36%.
modelo de suscetibilidade à erosão aplicado ao gerenciamento de linhas férreas. Estudo de caso: Malha Paulista - sp (Bacia Do Tietê - Sorocaba)
Keywords: Erosion; Geographic information systems (GIS); Geotechnologies; Hierarchical process analysis; Railways